EVALUASI PEMBELAJARAN TATAP MUKA TERBATAS DALAM MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK DI TK SE-KOTA PONTIANAK - Perdina, Siska; Prisuna, Bayu Fitra; Lukmanulhakim, Lukmanulhakim (Universitas Tanjungpura, 2024)
The aim of this research is to evaluate Limited PTM in improving children's cognitive development in kindergartens throughout the city of Pontianak. The approach and type of research used in this research is a quantitative approach with a survey research type. The population in the study were al kindergartens throughout the city of Pontianak with sampling using proportionate stratified random sampling and a sample of 30 TK/RA was obtained. Data colection techniques in this research used questionnaires, interviews, documentation. Before the instrument is used, validation is carried out through content validation by 2 validators who are considered experts using the Gregory test. The data analysis technique uses descriptive statistical data analysis techniques by converting respondent perception data into IKM intervals. The results of the research show that, learning management is 3.11 in the effective category, learning activities are 3.14 in the effective category, learning completeness is 3.20 in the effective category, learning facilities and infrastructure are 3.15 in the effective category. So the overal average is 3.15, which means the Limited PTM evaluation is in the